Development of Digital Modules of Comic-based Static Electricity Material Assisted by MOOCs Platform for Class XII High School Students - Cahyani, Diana Eka; Risdianto, Eko; Gunawan, Bodi (Jurnal Penelitian Pembelajaran Fisika, 2025)
This research is based on the unavailability of learning media that can increase students’ interest and motivation to learn physics. This study aims to describe the feasibility and describe student responses to the digital module of comic-based static electricity material assisted by the MOOCs platform. This research is development research with reference to the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research instruments used include expert validation questionnaires and student response questionnaires. The type of data used consists of quantitative data and qualitative data. This study obtained the results of the product feasibility validation assessment with an average percentage value of 89.36% which indicates that the comic-based digital module is very feasible to use. The increase in students concept understanding is included in the high category with an average percentage of 82.65% which shows that the use of comic-based digital modules assisted by the MOOCs platform is able to improve students concept understanding. The results of students’ responses obtained an assessment with an average percentage of 89.57% with the category of student responses to the development of comic-based digital modules, namely very good, which means that comic-based digital modules assisted by the MOOCs platform have attractiveness and positive responses for students. Based on the overall results of research and discussion, it is concluded that the digital module of comic-based static electricity material assisted by the MOOCs platform is suitable for use in physics learning.